(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Presents modern literature data on various aspects of the problem of endometrial hyperplastic processes. Some concepts of the development of this pathology are considered, information is provided on the risk of malignancy of various variants of endometrial hyperplastic processes and the main methods of treatment.